Flame retardant UV-curable acrylated epoxidized soybean oil based organic-inorganic hybrid coating - (:unkn) unknown (ELSEVIER SCIENCE SA, 2013)
Organic inorganic hybrid coating based on methacrylated/phosphorylated epoxidized soybean oil were obtained by combining photopolymerization and sol-gel process. A series of novel methacrylated and phosphorylated epoxidized soybean oil/silica coating materials were prepared from tetraethoxysilane (TEOS), and acrylated soybean oil via sol-gel technique. Acrylated epoxidized soybean oil (AESO) is obtained by reacting epoxidized soybean oil (ESO) with methacrylic acid and vinyl phosphonic acid. The characterization of AESO was performed by NMR and IR spectroscopy. In liquid form UV-curable, clear hybrid coating materials were applied on polycarbonate substrates then cured UV-light. Finally their coating performances were determined by the various tests methods hardness, gloss, cross-cut adhesion tests, stress-strain test, gel content, contact angle. Thermogravimetric analysis (TGA) showed that the incorporation of sal-gel precursor into the resin leads to an enhancement in the thermal stability and also flame retardancy properties of the coated material. The surface morphology of the hybrid coating was characterized by scanning electron microscopy (SEM). (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biodegredable; Low cost; Flame resistant; UV curing; Phosphorus; Epoxidized soybean oil; Sol-gel process; Hybrid coatings; EPOXY-RESINS; SILICON